The Food We Eat and the People Who Feed Us - Stephen Lee (Washington University Law Review, 2017)
Food justice scholars and advocates have made a simple but important point: for all the attention we pay to the food we eat, we pay far too little attention to the people who feed us. But can law play a role in directing consumer attention to labor-related issues? Traditional food law paradigms provide at best incidental benefits to food workers because these types of laws typically rely on transparency and disclosure schemes that serve narrow consumer-centric interests. An increasing number of laws attempt to disseminate information about the working conditions of the people who pick, process, and produce our food so that consumers can also consider the ethical and moral consequences of their food choices. In assessing this attempt to rebrand labor enforcement in consumer protection terms, this Article does two things. First, this Article identifies the conditions under which such schemes are most likely to succeed. Regulators should target food markets characterized by relative consumer wealth, norm consensus regarding which outcomes are desirable, and an established intermediation infrastructure to give disclosure laws the best chances for improving labor conditions along the food chain. Even where these conditions exist, a second point this Article makes is that disclosure laws should supplement, not supplant, traditional labor enforcement strategies that rely on worker- initiated complaints. This is because certain values, like autonomy, equity, and community standing are best vindicated by the workers themselves instead of by others (like consumers) on their behalf. Crowding out workers from the enforcement process creates the risk of exacerbating the structural forms of inequality that define work across the food system.
Keywords: Food justice; Consumer Safety and Health; Anti-Competition; Consumer Protection; Food law; Food safety law; labor-oriented consumer laws